1991
DOI: 10.1177/095632029100200110
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Efficacy of the Immunomodulatory Compound 7-thia-8-oxoguanosine in Coronavirus 229E Infections in Human Volunteers

Abstract: Intranasal 7-thia-8-oxoguanosine (NARI 10146) compared with placebo had no influence on the course of experimental coronavirus 229E infections in human volunteers. Possible reasons are discussed for the failure to confirm successful rodent experiments in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Another immunomodulator, a thioguanosine derivative, appeared to enhance the resistance of mice to coronavirus infection but did not appear to have the same effect in man at the doses used [67].…”
Section: Management and Therapymentioning
confidence: 90%
“…Another immunomodulator, a thioguanosine derivative, appeared to enhance the resistance of mice to coronavirus infection but did not appear to have the same effect in man at the doses used [67].…”
Section: Management and Therapymentioning
confidence: 90%
“…However, when given in the maximum acceptable dose to volunteers it did not improve the clinical or laboratory parameters of experimental influenza, even though the strain used was partly attenuated and the dose given was not large . A thioguanosine derivative has been found which protects mice against coronavirus infection by enhancing their resistance (rather than by a direct antiviral effect) and this has also been studied in volunteers using colds induced by a coronavirus; analysis indicates that either it was given in too low a dose, or that it does not enhance the primate response in the same way as that of the rodent (Higgins et al, 1991). In this field we are at a similar stage to that of work on interferons between 1957 and 1973 -we know that there are attractive theoretical possibilities but we do not know whether any such method can be made to work in man or what the 'benchmarks' for the properties of a candidate drug should be.…”
Section: (1) Transmissionmentioning
confidence: 99%
“…However, it has recently been shown that bradykinin, which can induce the symptoms of nasal irritation and discharge, is found in raised concentrations in the nasal secretions of individuals with rhinovirus colds (Naclerio et al, 1987;Proud et al, 1990). As antikinins are now being developed it is reasonable to investigate whether these relieve the symptoms and signs of a cold, but an initial study of one candidate, NPC 567, has been unsuccessful (Higgins et al, 1991).…”
Section: (5) Blockers Of Mediatorsmentioning
confidence: 99%
“…Pyrimidines, pyrimidinones and their derivatives are diazin heterocyclic compounds with important biological activity and pharmacological properties as effective bactericide and fungicide [1][2][3]. Pyrimido [4,5-b] [1,4]benzothiazines are an important class of fused heterocycles which have been described as being antiviral [4][5][6][7][8][9], antifungal [10] and enzyme inhibitor [11] agent. It is well known that mammalian lipoxygenases comprise a family of nonheme iron-containing enzymes which catalyze the stereospecific oxygenation of the 5-, 12-or 15-carbon atoms of arachidonic acid [12][13][14], oxidation of polyunsaturated fatty acids and esters to hydroperoxy derivatives [15].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison between some experimental vibrational wave number (Cm −1 ) according to Ref [29]. with calculated results for compounds[6][7][8] …”
mentioning
confidence: 99%